Reputasi Auditor dalam Manajemen Laba pada Food and Beverage di BEI - Layyina Humairoh; Hwihanus Hwihanus (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This study seeks to ascertain the impact of macroeconomic fundamentals, the configuration of ownership, the attributes of the company, and the composition of capital on the practice of earnings management, considering the reputation of the auditor as a moderating factor. This study employs data from 11 firms listed on the Indonesia Stock Exchange, chosen through purposive sampling over the years 2019 to 2022, resulting in a total of 44 instances of data observation. The analysis method uses SmartPLS analysis. The research results show that macro fundamentals, ownership structure, company characteristics and capital structure do not have a significant effect on earnings management. The composition of ownership and the financial leverage of a company notably impact its attributes. However, the standing of the auditor does not alter the effect that ownership configuration, company traits, and financial structuring have on the practices of earnings management.